Intranasal vaccination with murabutide enhances humoral and mucosal immune responses to a virus-like particle vaccine. - Erin M Jackson; Melissa M Herbst-Kralovetz (PLoS ONE, 2012)
Murabutide (MB) is a synthetic immunomodulator recognized by the nucleotide-binding oligomerization domain-containing protein 2 (NOD2) receptor on mammalian cells. MB has previously been approved for testing in multiple human clinical trials to determine its value as an antiviral therapeutic, and as an adjuvant for injected vaccines. We have found a new use for this immunomodulator; it functions as a mucosal adjuvant that enhances immunogenicity of virus-like particles (VLP) administered intranasally. MB enhanced Norwalk virus (NV) VLP-specific IgG systemically and IgA production at distal mucosal sites following intranasal (IN) vaccination. A dose escalation study identified 100 µg as the optimal MB dosage in mice, based on the magnitude of VLP-specific IgG, IgG1, IgG2a and IgA production in serum and VLP-specific IgA production at distal mucosal sites. IN vaccination using VLP with MB was compared to IN delivery VLP with cholera toxin (CT) or gardiquimod (GARD) and to parenteral VLP delivery with alum; the MB groups were equivalent to CT and GARD and superior to alum in inducing mucosal immune responses and stimulated equivalent systemic VLP-specific antibodies. These data support the further testing of MB as a potent mucosal adjuvant for inducing robust and durable antibody responses to non-replicating subunit vaccines.